Բացառիկ ժառանգություն (Դիվան Եղիա Մուշեղյանի. գիտական նկարագրություն) - Դանեղյան, Լորետա («Զանգակ - 97»)
For ihe first time a scientific description of a unique divan (nrchive) is presented in the article which is inherited to the generations by the 18th Century Armenian merchant, folklorist, social and political statesman Yeghia Kametsi Musheghyan. The divan is kept in Moscow "in the Archives of Foreign Policy of Russia". The divan, which is of a great scientific interest, includes letters, commercial and official documents, different collections (songbook, medical book, prayerbook, diclionary, translation etc.). The geometric boundaries of the materials used in the divan spread from Iran, Iraqi, India, Russia, Turkey to European countries etc. This valuable divan is worth the attention of large scientific areas. The article includes all 61 files of the divan.
Keywords: Հայ գրականություն; Պատմագրություն